Organizational Innovation and Human Resources Reform in Public Administration. Comparative View of Romania and France - Gabriela Cristina PATRASCU (Communications of International Proceedings, 2022)
The process of modernisation and transformation of public administration is all the more important as public administration contribute to the overall progress and wellbeing of a society. Several decades ago, many governments around the world have initiated public sector reforms, in an effort to find new ways of coping with ever growing and unprecedented difficulties, but have been unable to accomplish their work because of the outbreak of the pandemic. The main objective of this study is to present an analysis of various facets of human resources reforms and career development methods and the ways these methods have to be linked with the introduction of innovation within administrative organizations. At the same time the article explores and brings to attention the potential of “talent management” that is only tentatively applied by public administration managers, but that could be a very valuable practice within human resources management. In order to attain better results, the emphasis is placed on two administrative systems, namely Romania and France, whose administrative organization has several similarities that allow comparisons. The article draws mainly on the newest theoretical findings and qualitative results presented by the scientific literature on organizational innovation, public management and performance improvement.
Keywords: organizational innovation; human resources reform; talent management; resilience.